Influence of Achievement Motivation and Locus of Control Towards Competence of Lecturer Performance in AKUBANK ICM Cantrika Mitra Medan - Nur Aisyah (Analitika: Jurnal Magister Psikologi UMA, 2021)
This research discussed about lecturer competence in Akubank ICM Cantrika Mitra Medan of knowledge to develop increase the competence, namely by increasing education and training for lecturers who are still considered less competence. This study used quantitative methods, with questionnaires over 50 population. The Lecturer's performance is influenced by a number of factors, including (1) internal factors and (2) external factors. From the data found, motivation and locus of control tend to be "high" (53.33%). The average value of the overall cognitive abilities of lecturers is 81.92. Motivation and locus of control directly influences the performance of permanent lecturers. In other words, the better the support of motivation and locus of control, the higher the performance of permanent lecturers. Motivation and locus of control directly influence the performance of lecturers, all indicators in cognitive abilities are categorized as good, with indicators of the motivation of aspects of experience, skills and evaluations said to be good in constructing the variable motivation and locus of control.